Microbial life (Sinauer Associates, 2007)
Microbial Life captures the richness, the intellectual excitement, and present-day understanding of the role of the microbe in evolution, human health, and in our lives. It is written for sophomore to senior undergraduates who have a general understanding of chemical concepts and biochemistry. Rob Gunsalus, who has taught introductory microbiology at UCLA for 20 years, has joined the author team and is solely responsible for Parts II and III on physiology, growth, and metabolism. The Second Edition has been redesigned to help students study and learn more effectively. New pedagogical features include: redesigned chapter openers with clearly defined objectives; Section Highlights and Chapter Summaries that help students retain key information and terminology; an enhanced illustration program, with balloon captions that clarify complex processes and concepts; and icons directing students to additional resources on a new Companion Website.